Peri Implant Aesthetics – An Integrated Entity - Preeethika Guruprasath; Sai Sri Soury Geddam; P. L. Ravishankar (Peri Implant Aesthetics – An Integrated Entity, 2024)
Peri-implant esthetics encompasses the intricate interplay between soft and hard tissues surrounding dental implants, significantly influencing patient satisfaction and treatment success. This abstract delves into the integrated nature of peri-implant esthetics, highlighting the multifactorial considerations crucial for achieving optimal outcomes in implant dentistry. Soft tissue management, bone augmentation, implant placement, prosthetic design, gingival architecture, and patient maintenance are all key factors that play significant roles in peri-implant esthetics. This book underscores the holistic approach required to address the complexity of peri-implant esthetics, emphasizing the need for interdisciplinary collaboration and ongoing innovation to continually elevate standards of care and patient satisfaction in implant dentistry.